About some of the factors that led to the drying up of the Aral Sea (Texas Journal of Multidisciplinary Studies, 2022)
We know that for some reason something else appears or disappears. There are many such examples. In this article, we provide information on some of the factors that led to the formation of the Aral Sea, the second largest in the Eurasian continent.